(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article examines the emergence of the field of cognitive linguistics, the expression and application of the concepts of frame, scenario and concept, which are important elements of this field, in English and Uzbek. The research and conclusions of many linguists working in this field are analyzed.